2018
DOI: 10.2224/sbp.6618
|View full text |Cite
|
Sign up to set email alerts
|

Proactive personality and innovative behavior: The mediating roles of job-related affect and work engagement

Abstract: We examined the potential effects of job-related affect and work engagement as mediators in the relationship between proactive personality and innovative behavior. The Proactive Personality Scale, Positive and Negative Affect Schedule, Work Engagement Scale, and Innovative Behavior Scale were completed by 320 primary- and middle-school teachers in western China. Results showed that proactive personality was significantly and positively related to the teachers' innovative behavior. The effect of proactive pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 0 publications
3
53
1
8
Order By: Relevance
“…The current study’s findings indicate that Chinese nurses had a high level of work engagement, which contradicts past studies claiming lower work engagement among Chinese nurses due to high work pressures and imbalances between effort and reward ( Kong and Li, 2018 ; Wang et al, 2019 ). The reason for this difference could be explained by the present circumstances of the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study’s findings indicate that Chinese nurses had a high level of work engagement, which contradicts past studies claiming lower work engagement among Chinese nurses due to high work pressures and imbalances between effort and reward ( Kong and Li, 2018 ; Wang et al, 2019 ). The reason for this difference could be explained by the present circumstances of the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance, Grant and Ashford (2008) presented a proactivity process perspective, arguing that proactive individuals anticipate future events and are mindful of the effects of their actions. Previous empirical research, albeit limited, points toward this direction, since some prior studies have reported positive links between proactive personality and individual and team innovative performance (Chen et al, 2013;Li et al, 2017;Parker et al, 2006). Taking into account this initial evidence along with the inherent relevance of proactive personality to enacting change and innovation related behaviors we hypothesized that:…”
Section: Several Authors Have Acknowledged This Literature Void and Cmentioning
confidence: 98%
“…Previous primary research, albeit limited, consistently suggests that proactive personality is positively linked to innovative behaviors at work, (Fuller & Marler, 2009;Potočnik et al, 2015). Although, most criteria-related validity studies of proactive personality are focused on creativity (e.g., Fuller & Marler, 2009;Gong, Cheung, Wang, & Huang, 2012;Li, Liu, Liu, & Wang, 2017).…”
mentioning
confidence: 99%
“…The main dimensions forming this working status are vigour (high vitality and good resilience when working), dedication (loving the job and feeling the high sense of working honour) and absorption (being concentrated in working and not willing to get out; Seppälä et al, ). Compared with other countries, the work and engagement level of Chinese registered nurses is lower, because of the shortage of nurses, high working pressure and the imbalance of payment and reward as well (Kong & Li, ). So their willingness to pay much time and vigour in nursing is weak, resulting in their job burnout (Havens, Gittell, & Vasey, ).…”
Section: Introductionmentioning
confidence: 99%